Medical Informatics Training and Research at Rennes University School of Medicine - Beux, P. Le; Burgun, A.; Jarno, P.; Siregar, P. (Yearbook of Medical Informatics, 1998)
The University of Rennes Medical School has offered Medical informatics training since 1988; at the same time, research in medical informatics was started. This paper describes the teaching programs at both the undergraduate level and at the graduate level. Research topics comprise fundamental research on biomedical models, ontologies for medical knowledge representations, natural language processing, and research for diagnosis and therapeutic aids. We have developed a local area network which communicates between the School of Medicine and the University Hospital, both internally (Intranet) and externally by access to the National Research network (RENA TER) in France, which is connected to the internet.
Keywords: Medical Informatic; Education; Training; Graduate Program; Research